Pengembangan Program Aplikasi Komputer untuk Mengolah Data Uji Bioekivalensi - Sukmadjaja Asyarie; Lucy Dewi Nurhayati Sasongko; Yusrani Salman (Jurnal Matematika & Sains, 2006)
A computer application program for processing plasma/serum drug concentration data for bioequivalence test according to the Bioequivalence Study Guideline of The National Agency of Drug and Food Control of The Republic of Indonesia 2004, had been developed using Microsoft® Visual Basic 6.0. The program developed was used to process bioequivalent parameters using eight sets of plasma drug concentration data, and the results were compared to that of manual calculation using Microsoft® Excel 2003 program. Result showed that bioequivalence parameters calculated by this program were similar to those calculated by Microsoft®  Excel 2003.